A National Policy Study on Child Labour and Development in the Philippines - Leonardo Lanzona; Fernando T. Aldaba; Ronald J. Tamangan (Philippine Institute for Development Studies (PIDS), 2004)
The alarming number of children engaged in labor as released by the National Statistics Office from the years 1995 to 2001 gave rise to a timely national policy study to review all the important studies available on child labor and assess key government policies affecting child labor in the Philippines. The paper provides an overview of the nature, extent and predominant forms of child labor in the country based on available data disaggregated by age, sex, geographic distribution, industry, and occupation. Previously done literature about child labor is examined to identify determinants as to why children work despite low wages and poor working conditions and the possible consequences and implications socially and economically. A review of the international and national policies operating in the Philippines concerning child labor is conducted to identify best practices and replicable approaches as well as to assess the adequacy of policy responses in eliminating child labor. The paper ended with proposals and recommendations on what else needs to be done and an agenda for possible future researches.
Keywords: 330; child labor; labor policies; International Labour Organization (ILO)